Future Directions for Car Parts Remanufacturing Business: Research Results - Monika KOSACKA-OLEJNIK; Angelina MURAWIŃSKA; Magdalena PASZKIEWICZ; Milena ZAREMBA (Communications of International Proceedings, 2021)
Remanufacturing has recently received significant interest because of its environmental and economic benefits so it is seen as a preferable waste management option, in particular relevant in the automotive sector. Considering the literature review analysis, it was noticed that there has been still limited knowledge on the characteristics of the market for remanufactured products. In this paper there are analyzed customer-related factors which have an impact on polish remanufacturing business. These factors include:  remanufacturing awareness, remanufacturing motives, product knowledge, product opinion, vehicle use pattern and customer’s preferences. On this basis there was prepared a survey conducted among potential remanufactured product customers in Poland. Results show guidelines for remanufacturing in the automotive sector.
Keywords: Remanufacturing; Automotive Industry; Stakeholders; Customer-Orientation